2005
DOI: 10.3200/jach.54.2.87-94
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Motivation for Physical Activity: Differentiating Men's and Women's Motives for Sport Participation and Exercise

Abstract: Despite the many clear benefits of an active lifestyle, lack of physical activity is a significant health problem in the college population. A key issue in physical activity research is developing an understanding of motivation. Although physical activity takes many forms, most research designed to enhance motivation for and adherence to physical activity focuses on exercise behavior and ignores sport participation. In this study, the authors compare motivations for sport participation versus exercise among co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
441
9
47

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 579 publications
(543 citation statements)
references
References 1 publication
46
441
9
47
Order By: Relevance
“…Some prefer attending an exercise facility, while others prefer organized sports. Individuals and their personality characteristics will determine what style of exercise they prefer, but previous studies have found a link between intrinsic motivation and sport participation (Kilpatrick et al, 2005). These findings suggest that including sports activities in health promotion programs may be valuable to increasing individuals' participation in exercise activities.…”
Section: Implications and Future Research Directionsmentioning
confidence: 68%
See 2 more Smart Citations
“…Some prefer attending an exercise facility, while others prefer organized sports. Individuals and their personality characteristics will determine what style of exercise they prefer, but previous studies have found a link between intrinsic motivation and sport participation (Kilpatrick et al, 2005). These findings suggest that including sports activities in health promotion programs may be valuable to increasing individuals' participation in exercise activities.…”
Section: Implications and Future Research Directionsmentioning
confidence: 68%
“…Previous research (Kilpatrick, Hebert, & Bartholomew, 2005) has shown that students were more intrinsically motivated toward sport participation, but more extrinsically motivated toward exercise. Kilpatrick et al (2005) also found that increased maintenance and adherence to exercise behaviors were associated with intrinsic motivation. These findings suggest that there is a need to understand individuals' various motivations for exercise, and that focusing on areas in which people are intrinsically motivated may maximize the effectiveness of an exercise program.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the literature have indicated that a big majority of students who come to the university have stopped participating in the sport, and after college graduation, almost half of these students have left sport or exercise (Kilpatrick et al, 2005). Determination of the motivations that are active in sport participation is important because these motives can increase the participation of individuals in physical activity (Del Pilar Vílchez & De Francisco, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Gaston-Gayles (2004) also found that an opportunity to play professionally was a motive to play sports at the college level, which was a more prominent factor among male athletes. Kilpatrick et al (2005) used the Exercise Motivation Inventory-2 to determine the differences between males and females and motivational differences between exercise and sport. Affiliation, enjoyment, challenge, and competition were the top motivators for sport in a sample of college students (not college athletes).…”
Section: College Sport Motivationmentioning
confidence: 99%